Proceedings of the 33rd Annual Conference on Design Automation Conference - DAC '96 1996
DOI: 10.1145/240518.240605
|View full text |Cite
|
Sign up to set email alerts
|

Identifying sequential redundancies without search

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…For RID, only techniques that are based on uncontrollability and unobservability analysis are reviewed. A detailed review of other RID techniques can be found in [14]. …”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…For RID, only techniques that are based on uncontrollability and unobservability analysis are reviewed. A detailed review of other RID techniques can be found in [14]. …”
Section: Preliminariesmentioning
confidence: 99%
“…Otherwise, faults that can be detected by (sequential) multiple path sensitization would be marked as unobservable. In [14], a sequential redundancy identification procedure, FIRES, was proposed. FIRES applies sequential uncontrollability/unobservability on every fanout stem and finds c-cycle redundant faults for which a conflicting value assignment on the stem is necessary for detection.…”
Section: Identifying Sequentially Redundant and Untestable Faultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another notion of equivalence was suggested in [7] which was used for sequential resynthesis by redundancy removal in [8]. Their notion of redundancy results in replacements which are not 0-cycle delay-safe replacements [9]; it has not been shown that if their replacements are n-cycle delay-safe replacements, neither what this n might be. A sequential resynthesis technique relevant to our model is retiming and resynthesis [10].…”
Section: Introductionmentioning
confidence: 99%